A Comparative Clinical Study on Effect of Vasa Guggul and Chinnodbhava Kwath in the Management of Amlapitta - Villas, Babar Vitthalrao (International Research Journal of Ayurveda & Yoga, 2022)
Background: In the 21st century the era of competition life it is full with stress having more speed and accuracy are the prime demands. The needs of the human being are infinite but the availability is less to fulfil the growing needs which have no end. Nowadays the people are attracted towards the junk foods; they are changing their diet pattern, life style and behavioural pattern, working with stress and strain. So, the people are becoming stressful with worry, tension, and anxiety causing so many psychological disorders, which hampers the digestion and is causing acidity, gastritis, dyspepsia, ulcer and anorexia. All these symptoms can be covered under the broad umbrella of Amlapitta in Ayurveda. In the nidanas of the Amlapitta mainly causing dietary factors, addiction of alcohol, tobacco chewing, or smoking are chiefly associated ones and commonly found. Aim: To assess the clinical efficacy of vasa guggul and chinnodbhava kwath in the management of amlapitta. Materials and Methods: The clinical studies were conducted by the random comparative method; this method compared the clinical efficacy of vasa guggul and chinnodbhava kwath in the management of amlapitta. Result: In Group A (Vasa Guggul) 3 Patients (15%) and Group B (Chinnodbhava Kwath) 10 Patients (50%) were shown marked improvement. Conclusion- Hence Both the Drugs gave good improvement in both groups. But test Group B (Chinnodbhawa Kwath) is slightly more effective than Group A (Vasa Guggul).